Growth and Yield Studies in the Pure Even-aged Plantations in IGNP Area of Rajasthan for their Sustainable Management - Tewari, V P (Annals of Arid Zone, 2016)
Growth and yield studies based on the permanent sample plot (PSP) data are required for the sustainable management of plantations. In this study, volume functions, site index equations, potential stand density, stem number and basal area development models in pure even-aged stands of Dalbergia sissoo, Tecomella undulata and Eucalyptus camaldulensis planted in IGNP area of Rajasthan have been developed. Various volume equations were tried to arrive at the best equation for predicting volume yield in the stands. The volume equations assume importance in projecting the total volume at different stages as the plantations mature. Some base-age variant and invariant site-index models were used and compared for their relative accuracy to assess the productive capacity of the sites in relation to different tree species. Relationships between quadratic mean diameter and stems ha-1 were developed to establish the limiting density line which is useful in generating information about the maximum number of trees ha-1 that can be retained in the stands at a given mean stand diameter. Two different models were compared to describe the mortality and the model with site index as one of the variables performed better compared to the model without site index. Seven different stand level models also were compared for predicting basal area in the stands. The models tested belong to the path invariant algebraic difference form of a non-linear model and can be used to predict future basal area in the stands. These can be used to analyze the relationship between stand density and tree growth. In combination with the stand density model, the proposed basal area models may also be used to define the type and weight of thinnings in the stands and are crucial for evaluating different silvicultural treatment options. The performance of the models was compared using different quantitative tests and best models were selected based on the fit statistics and model evaluation criteria for their wider applicability and sustainable management of D. sissoo, T. undulata and E. camaldulensis plantations in the study area. Key words: Growth and yield models, model evaluation, IGNP area, D. sissoo, T. undulata, E. camaldulensis.